Answer:
![\boxed{ \bold{ \huge{ \boxed{ \sf{ \sqrt{130} \: \: units}}}}}](https://tex.z-dn.net/?f=%20%20%5Cboxed%7B%20%5Cbold%7B%20%5Chuge%7B%20%5Cboxed%7B%20%5Csf%7B%20%5Csqrt%7B130%7D%20%20%5C%3A%20%20%5C%3A%20%20units%7D%7D%7D%7D%7D)
Step-by-step explanation:
Let the points be A and B
Let A ( 1 , 3 ) be ( x₁ , y₁ )and B ( -6 , -6 ) be ( x₂ , y₂ )
<u>Finding </u><u>the </u><u>distance</u><u> </u><u>between </u><u>these</u><u> </u><u>points</u>
![\boxed{ \sf{distance = \sqrt{ {(x2 - x1)}^{2} + {(y2 - y1)}^{2} } }}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Csf%7Bdistance%20%3D%20%20%5Csqrt%7B%20%7B%28x2%20-%20x1%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y2%20-%20y1%29%7D%5E%7B2%7D%20%7D%20%7D%7D)
![\longrightarrow{ \sf{ \sqrt{ {( - 6 - 1)}^{2} + {( - 6 - 3)^{2} } }}}](https://tex.z-dn.net/?f=%20%5Clongrightarrow%7B%20%5Csf%7B%20%5Csqrt%7B%20%7B%28%20-%206%20-%201%29%7D%5E%7B2%7D%20%2B%20%20%7B%28%20-%206%20-%203%29%5E%7B2%7D%20%20%7D%20%7D%7D%7D)
![\longrightarrow{ \sf{ \sqrt{ {( - 7)}^{2} + {( - 9)}^{2} } }}](https://tex.z-dn.net/?f=%20%5Clongrightarrow%7B%20%5Csf%7B%20%5Csqrt%7B%20%7B%28%20-%207%29%7D%5E%7B2%7D%20%2B%20%20%7B%28%20-%209%29%7D%5E%7B2%7D%20%20%7D%20%7D%7D)
![\longrightarrow{ \sf{ \sqrt{49 + 81}}}](https://tex.z-dn.net/?f=%20%5Clongrightarrow%7B%20%5Csf%7B%20%5Csqrt%7B49%20%2B%2081%7D%7D%7D%20)
units
Hope I helped!
Best regards! :D
Answer:
Step-by-step explanation:
Option A
9.21 * 10³ = 9,210 ≠ 921
Option A is FALSE.
Option B
9.21 * 10¹ = 92.1
Option B is TRUE.
Option C
0.921 * 100 = 92.1 ≠ 921
Option C is FALSE
Option D
0.921 * 10⁴ = 9,210
Option D is TRUE
Option E
0.0921 * 10² = 9.21
Option E is TRUE
Answer:
its 5 m/minute
Step-by-step explanation:
you have to use the units that are given in the equation
pls mark brainliest if you geel like it...
Answer:
can u help answer mine
Step-by-step explanation:
Step-by-step explanation:
Q1 . (f+g)(x) = f(x) + g(x)
=4x-4 +2x^2 -3x
= 2x^2 + x -4
Q2. (f-g)(x) = f(x) - g(x)
= 2x^2−2 - (4x+1)
= 2x^2 -2 -4x -1
= 2x^2 - 4x -3
Q3. h(x)=3x−3 and g(x)=x^2+3
(h.g)(x) = h(x) × g(x)
= (3x-3) × (x^2 + 3)
=3x^3 -3x^2 + 9x -9
Q4.f(x)=x+4 and g(x)=x+6
(f/g)(x) = f(x) ÷ g(x)
= x+4 / x+6
the domain restriction is x>-6
x<-6
x doesn't equal (-6)